Highlights of the Faraday Discussion on Nanoparticle Synthesis and Assembly, Argonne, USA, April 2015. Issue 72 (18th September 2015) - Lin, Xiao-Min; Sun, Yugang; Shevchenko, Elena V.; Sankaranarayanan, Subramanian K. R. S.; John, Daniela; Fedin, Igor; Bresme, Fernando; Möhwald, Helmuth; Moriarty, Philip; Sorensen, Christopher M.; Law, Bruce M.
<x xml:space="preserve">Abstract</x>